Antitumour activity of a combined treatment with PMEDAP and docetaxel in the Prague inbred Sprague-Dawley/cub rat strain bearing T-cell lymphoma - Bobkov, K; Gut, I; Mandys, V; Holý, A; Votruba, I; Otová, B (Anticancer research, 2001)
Antitumour efficiency of combined therapy with N-9-[2-(phosphonomethoxy)ethyl]-2,6-diaminopurine (PMEDAP) and docetaxel (DTX) was studied in an in vivo model of s.c. transplanted Sprague-Dawley (SD/Cub) rat T-cell lymphoma (phenotype SD10/96). The effect of the combined treatment of DTX with PMEDAP was significantly higher than that of DTX or PMEDAP alone. The s.c. administration of DXT into the vicinity of growing lymphoma together with i.p. administration of PMEDAP was found to be the most efficient combination. In this case, two out of four rats did not develop any lymphoma and remained alive. An irregular expression of Bcl2 protein was found in untreated and treated lymphomas, while the expression of protein p53 as well as MDM2 was not observed. All three types of the above-mentioned treatments (PMEDAP, DXT, DXT+PMEDAP) increased significantly the number of p21-positive cells, compared with untreated tumours.
Keywords: Adenine; paclitaxel; Rats; taxoidy; Lymphoma, T-Cell; potkani Sprague-Dawley; Neoplasm Transplantation; Disease Models, Animal; Docetaxel; Taxoids; mužské pohlaví; injekce intraperitoneální; adenin; Drug Synergism; fytogenní protinádorové látky; Injections, Subcutaneous; docetaxel; krysa rodu Rattus; Injections, Intraperitoneal; modely nemocí na zvířatech; synergismus léků; ženské pohlaví; zvířata; transplantace nádorů; Antineoplastic Combined Chemotherapy Protocols; lymfom T-buněčný; Rats, Sprague-Dawley; Antineoplastic Agents, Phytogenic; protokoly protinádorové kombinované chemoterapie; injekce subkutánní; Paclitaxel; Female; Male; Animals